Proposed improvement of service quality in a university canteen using Servperf, PGCV, and TRIZ methods - Anggraeni, Shanti Kirana; Wahyuni, Nuraida; Amanah, Umi Noer; Febianti, Evi; Ekawati, Ratna (Universitas Sultan Ageng Tirtayasa, 2023)
Kantin Hijrah at FT Untirta is among the food and beverage businesses located at the Faculty of Engineering, Sultan Ageng Tirtayasa University. Continuous efforts are essential to enhance service quality to achieve satisfied and loyal customers. This study aims to assess the service quality at Kantin Hijrah FT Untirta and suggest improvements by utilizing the SERVPERF, PGCV, and TRIZ methods. Questionnaires were distributed to 97 active FT Untirta students for data collection. According to the SERVPERV method, the service quality yielded a score of 3.64, indicating satisfaction. Additionally, utilizing the PGCV and TRIZ methods identified five attributes for improvement: maintaining cleanliness in the restroom, ensuring a well-kept handwashing area, providing menu books, adequate and well-maintained tables, and chairs, and ensuring the overall comfort of Kantin Hijrah (i.e., maintaining a suitable temperature and reducing noise). Implementing these proposed improvements aims to further enhance the service quality at Kantin Hijrah.